Tindak Tutur Ekspresif Dan Strategi Kesopanan Dalam Naskah Drama Julius Caesar Oleh Shakespear - Ruslani, Mohamad Zuhri (2016)
The purpose of this study identify forms of expressive speech contained in the plays by Shakespeare's Julius Caesar and identify forms of politeness speech contained in the plays by Shakespeare's Julius Caesar. The method used in this study is a qualitative research method. Techniques of data collection by using the technique see, also used the technique noted. Analysis of data analysis techniques used in this study using a unified method and the method of ekstralingual intralingual. Results from this study is, in the form of expressive speech utterances are kind of expressive blame, expressive speech praising, pleading expressive speech, expressive speech satirical and expressive speech reminded. While the speech politeness by Leech, there is a maxim of politeness speech award (approbation maxim), the maxim of simplicity (modesty maxim) maxim agreement (agreement maxim), and the maxim kesimpatisan (sympath maxim). They found expressive speech acts 2 findings, expressive speech praised the three findings, expressive speech pleading 1 findings, expressive speech quipped 1 findings and expressive speech reminiscent 3 findings. Is also found that the speech politeness in the text of Julius Caesaroleh Shakespear there are three findings maxim of Choice (Approbation Maxim), two findings maxim Modesty (Modesty Maxim), two findings maxim Covenant (Agreement Maxim), and 2 findings maxim Kesimpatisan (Sympath Maxim ).